Waveguide-Type Directional Coupler Based on Substrate Integrated Waveguide (SIW) - Zohreh Pourgholamhossein; Reza Safian (Journal of Intelligent Procedures in Electrical Technology, 2012)
Substrate Integrated Waveguide (SIW) is a new type of guided wave structure which could be implemented in both microwave and millimeter wave integrated circuits. In this paper a novel waveguide type directional coupler based on substrate integrated waveguide consisting a double layer dielectric substrate is proposed. The design process is carried out using coupling theory and Chebyshev method. The proposed structure is fully based on SIW structure except at the input-output ports which are microstrip lines. The SIW bends are optimized for the lowest insertion loss using HFSS software. The center frequency of designed 20dB coupler is at 10GHz with 6GHz bandwidth. Based on the simulations the coupling remains almost constant over the coupler bandwidth with less than 2 dB variations. Larger bandwidth can be achieved by increasing the number of apertures. Also if we used a second set of apertures opposite side wall, the coupling would be increased by 6 dB.